Compositional design of Fe-based multi-component bulk metallic glass based on CALPHAD method. (15th July 2017) - Han, J.J.; Wang, C.P.; Wang, J.; Liu, X.J.; Wang, Y.; Liu, Z.K.
Abstract: A quantificational composition design protocol (CDP) of Fe-based bulk metallic glasses (BMGs) with excellent glass-forming ability (GFA) has been proposed on the basis of the thermodynamic calculations. The stability of liquid and the crystallization of solids were both evaluated from the perspective of atomic structure and local composition. The present protocol successfully associates the stability of liquid to the melting point of alloy and the difficulty of crystallization by considering the type and competition of potential equilibrated phases. Specifically, this protocol provided the selection criteria of phases and elements from the viewpoint of structure and composition fluctuations during nucleation for each phase, whose accuracy and effectiveness were experimentally verified. Graphical abstract: Highlights: An accurate and effective composition design protocol for Fe-based multi-component bulk metallic glass was firstly proposed The protocol emphasizes the process of nucleation other than the melting point that is focused before Selection principles of phases and sixteen elements are tabulated and facilitate the composition design